Monocyte esterase deficiency in gastrointestinal cancer. Issue 6 (June 1993) - Markey, G M; Curry, R C; Swain, D; Morris, T C; McCormick, J A; Alexander, H D; Edgar, S
Abstract : AIM–To substantiate the high incidence of monocyte esterase deficiency (MED) in gastrointestinal carcinoma already reported in a small group of patients; to compare the clinical findings in esterase deficient and esterase positive patients. METHODS–Peripheral blood smears (n = 22) or cytocentrifuge preparations (n = 52) of mononuclear cells from the peripheral blood of patients with gastrointestinal carcinoma were stained by the non-specific esterase stain (pH 5.8) using a batch technique. Samples containing > or = 85% esterase negative monocytes were identified at light microscopic examination. RESULTS–Seven of 74 patients were identified as having MED. This correlated exactly with the proportion (five of 46) found before, using an automated method, and was significantly higher than the 0.8% incidence in normal blood donors shown in that study. Comparison of the clinical details of the 12 MED patients with those of 105 esterase positive patients showed a significantly longer disease free survival in the MED cohort and increased occurrence of benign neoplasms–largely colorectal polyps–in this group also. Three patients had a borderline degree of deficiency and were excluded from comparisons, although they showed the same clinical tendencies as the MED group. CONCLUSIONS–There is a strong degree of association between monocyte esterase deficiency and gastrointestinal carcinoma. Further evidence must be sought to prove that the deficiency precedes the disease and therefore may predispose to it, or at least may identify subjects with such a predisposition. This could lead to early diagnosis and effective treatment of gastrointestinal carcinoma in a sizeable proportion of patients.